Spectrum of external catheter-related infections in children with acute leukemia-Single-center experience - M. Zachariah; L. Al-Yazidi; W. Bashir; A.H. Al Rawas; Y. Wali; A.V. Pathare (Elsevier, 2014)
Background: External catheters (ECs) are commonly used in children who are receiving treatment for acute leukemia. Aims: To study the spectrum of microorganisms and to compare the rates of infection. Methods: A total of 42 ECs were inserted, including 28 Port-A-Caths, 11 CVC lines and 3 Hickman lines. Single ECs were required for 19 patients (45.2%), whereas 2, 3 and 4 ECs were required in 8, 1 and 1 patients, respectively. Results: Overall, 37 culture-documented infections were present in 18 (62%) patients who had ECs. Gram-positive microorganisms were identified in 20 cases, Gram-negative microorganisms in 14 cases and fungal infections in 3 cases. Of the 42 devices implanted, 10 out of 28 Port-A-Caths (35.7%), 2 out of 3 Hickman catheters (66.7%) and 9 out of 11 central venous catheters (81.8%) required removal due to infection. The average length of working life for the ports was 330.6 days (range: 40-1043 days). The median rate of complications due to infection was 2.84 infections per 1000 catheter days (interquartile range: −1.55 to 5.8), and the number of infections was correlated with the number of ports (Pearson's r = 0.51; p < 0.05). Keywords: Acute leukemia, Infection, Culture, Catheter, Port-A-Cath, Hickman